2012
DOI: 10.1088/2041-8205/759/2/l37
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Water Vapor in a Pre-Stellar Core

Abstract: Water is a crucial molecule in molecular astrophysics as it controls much of the gas/grain chemistry, including the formation and evolution of more complex organic molecules in ices. Pre-stellar cores provide the original reservoir of material from which future planetary systems are built, but few observational constraints exist on the formation of water and its partitioning between gas and ice in the densest cores. Thanks to the high sensitivity of the Herschel Space Observatory,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
221
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(238 citation statements)
references
References 49 publications
12
221
5
Order By: Relevance
“…This is likely due to the L1544 lines presenting two closeby velocity components (Hily-Blant et al 2010b), which are not resolved in the C 15 N spectrum. These two velocity components may be related to the collapse signature recently evidenced by the inverse P-Cygni profile of a water line (Caselli et al 2012).…”
Section: Resultsmentioning
confidence: 69%
“…This is likely due to the L1544 lines presenting two closeby velocity components (Hily-Blant et al 2010b), which are not resolved in the C 15 N spectrum. These two velocity components may be related to the collapse signature recently evidenced by the inverse P-Cygni profile of a water line (Caselli et al 2012).…”
Section: Resultsmentioning
confidence: 69%
“…In addition, low-mass protostellar objects tend to have an outer abundance of ∼ 10 −8 (Van Dishoeck et al 2011) or even lower (3 × 10 −10 , Mottram et al 2013). Moreover, Snell et al (2000) or Caselli et al (2012) have estimated very low abundances (10 −10 − 10 −8 ) in cold regions. Hence the value derived in our study is compatible with what is found in cold outer regions.…”
Section: The Warm Protostellar Envelopementioning
confidence: 99%
“…Nonthermal desorption by FUV photons can also be efficient, as shown by laboratory experiments (Öberg et al 2009b,c). Nonthermal desorption dominates in colder regions, either UV-shielded dense cores where secondary UV photons are produced by the interaction between cosmic rays and H 2 molecules (e.g., Caselli et al 2012), or in low-UV-field illumination photo-dissociation regions, where dust grains are too cold to sublimate their ices. This is the case of the Horsehead, where the combination of a moderate-radiation field (χ = 60 relative to the Draine field; Draine 1978), and high density (n H ∼ 10 4 −10 5 cm −3 ) implies low dust grain temperatures, from T dust ∼ 30 K in the outer PDR to T dust ∼ 20 K slightly deeper inside the cloud (Goicoechea et al 2009a).…”
Section: Introductionmentioning
confidence: 99%